REMOVAL OF REACTIVE DYE REMAZOL BRILLIANT BLUE R FROM AQUEOUS SOLUTIONS BY USING ANAEROBICALLY DIGESTED SEWAGE SLUDGE BASED ADSORBENTS - Ozcimen, Didem; Salan, Tufan (ASSOC CHEMICAL ENG, 2016)
In this study, adsorbents were produced from sewage sludge via chemical and thermal activation processes. Experiments were carried out in a tubular furnace at a heating rate of 20 degrees C min(-1) and temperature of 550 degrees C with a nitrogen flow rate of 400 mL min(-1) for 1 h. Dye adsorption experiments were performed with Remazol Brilliant Blue R at several concentrations under batch equilibrium conditions by comparing sewage sludge based adsorbents with raw material and a commercial activated carbon. Maximum adsorption capacities of carbonized sewage sludge (CSWS) and activated sewage sludge (ASWS) were found as 7413 and 9.376 mg g(-1) for 100 mg L-1 dye solution, whereas commercial activated carbon had a capacity of 11.561 mg g(-1) Freundlich and Langmuir isotherms were used to explain the adsorption mechanism together with pseudo-first-order and pseudo-second-order kinetic models. The Langmuir isotherm, which had adsorption capacities of 34.60 (CSWS) and 7299 mg g(-1) (ASWS), provided a better fit to the equilibrium data than that of the Freundlich isotherm. The pseudo second-order model, which had adsorption capacities of 7451 (CSWS) and 9.319 mg g(-1) (ASWS), was very favorable to explain the adsorption kinetics of the dye with high regression coefficients.
Keywords: sewage sludge; carbonization; activated carbon; adsorption; Remazol Brilliant Blue R; LOW-COST ADSORBENTS; WASTE; WATER; BIOSORPTION; COMPOSITE; DEGRADATION; SORPTION; ORANGE; Chemistry; Engineering